The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0193945919838990
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study on Patient Safety Culture, Patient Safety Competency, and Adverse Events

Abstract: This study aims to examine the associations between nurses’ perceptions of patient safety culture, patient safety competency, and adverse events. Using convenience sampling, we conducted a cross-sectional study from February to May 2018 in two university hospitals. Furthermore, we performed multiple logistic regression to examine associations between patient safety culture, patient safety competency, and adverse events. Higher mean scores for “communication openness” in patient safety culture were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 31 publications
(51 reference statements)
3
73
2
Order By: Relevance
“…In turn, a non‐punitive patient safety culture allows for a mutual trust environment in which to report, share and learn from mistakes (Lin, Lin, & Lou, 2017). As a result, staff's perceptions of patient safety are promoted, all of which also leads to patient safety (Abusalem et al., 2019; Han, Kim, & Seo, 2020; Wang et al., 2014). A similar result was consistent with other Chinese studies indicating an improvement in patient safety culture could lead to a decrease in adverse events or an increase in adverse event reporting in hospitals (Hong & Li, 2017; Wang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, a non‐punitive patient safety culture allows for a mutual trust environment in which to report, share and learn from mistakes (Lin, Lin, & Lou, 2017). As a result, staff's perceptions of patient safety are promoted, all of which also leads to patient safety (Abusalem et al., 2019; Han, Kim, & Seo, 2020; Wang et al., 2014). A similar result was consistent with other Chinese studies indicating an improvement in patient safety culture could lead to a decrease in adverse events or an increase in adverse event reporting in hospitals (Hong & Li, 2017; Wang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are considered a key patient safety link between patients and other health professionals and have an important role in promoting safety issues and improving patient outcomes (Sim et al., 2019). Individual nurses hold attitudes towards safety practices that may influence patient outcomes (Han et al., 2020). These attitudes are referred to as safety attitudes and relate to an individual's beliefs, perceptions, feelings or thinking towards safety practices, procedures and policies (Sexton et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified that nurse staffing and the nursing work environment can impact on patient outcomes (Lee et al., 2018; Stalpers et al., 2015). Nurses' safety attitudes are also thought to influence patient outcomes (Han et al., 2020). The RN4CAST research programme in Europe (conducted in 243 hospitals in six countries) identified that one in three nurses ( N = 13,077 nurses) were reported to have poor safety attitudes (Aiken et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, anaesthesia‐related mortality is higher in developing countries than in developed countries (Bainbridge et al., 2012 ). Also, patient safety culture scores have been found to be negatively correlated with AEs incidence (Han et al., 2020 ; Mardon et al., 2010 ; Najjar et al., 2015 ), and Japan was reported to have a lower score for patient safety culture than the United States (Fujita et al., 2013 ). In Japan, medical policy promotes an error‐based incident reporting system, but, on the other hand, few studies have focussed on AEs that are important for patients.…”
Section: Introductionmentioning
confidence: 99%